Decreasing time on sick leave for patients with heart failure in Sweden during two decades. (14th October 2021) - Ekestubbe, S; Giang Kok, W; Lindgren, M; Rosengren, A; Schioler, L; Schaufelberger, M
Abstract: Background: Heart failure (HF) is increasing in people of working age in Sweden (1). Given high morbidity and reduced quality of life among HF patients (2, 3), working capacity could be greatly affected, however, studies are scarce. Purpose: To determine trends in sick leave rates following a first hospitalization for HF in Sweden 1995–2015 compared to controls matched by age and sex. Methods: In Sweden, people who cannot work receive sickness benefit. Sickness benefit pay days are registered by Statistics Sweden. We identified all patients aged 18–60 years with a first hospitalization for HF in Sweden 1995–2012 in the National Patient Register (NPR). For each case we selected 2 controls matched for age and sex. Cases and controls were split into age groups, <45 years and 45–60 years. Age, sex and comorbidities were recorded. Paid sickness benefit days were recorded during the index year and the two subsequent years. Results: A total of 24, 677 cases and 65, 923 controls were included, mean age for the younger and older age group 36.6 and 54.5 years, and proportion of women 35.3% and 23.8%, respectively. In 1995, the proportion of time on sickness benefit in patients <45 years was on average 28%, decreasing to 15% in 2012, with corresponding estimates for patients 45–60 29% and 17%, shown by index year for cases and controls for patients <45 years in Figure 1 and for patients 45–60 years in Figure 2. Conclusion: Patients had a longer time on sick leave than controls over the study period. Time on sickness benefit initially declined over the course of the study period for both patients and controls, but the last years of the study period this decline stalled for both patients and controls. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the Swedish state under an agreement between the Swedish government and the County Councils Concerning Economic Support of Research and Education of Doctors [ALFGBG-717211, ALFGBG-433211, ALFGBG-725081]; the Swedish Heart and Lung Foundation [2013-0307, 2018-0419, 2018-0589].